VD_FINDINFO HC / 2014 / 685 vom 5. November 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, LOCAL PROFESSIONNEL, LOYER INDEXÉ, LOYER ÉCHELONNÉ, ABUS DE DROIT | 2 al. 2 CC, 20 al. 2 CO, 269b CO, 269c CO